2018
DOI: 10.1016/j.jclepro.2017.11.138
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of sophorolipids from stearic acid by solid-state fermentation, a cleaner alternative to chemical surfactants

Abstract: In this manuscript, we approach the production of biosurfactants as a cleaner alternative to the chemically-produced surfactants currently used in a wide range of industries. Sophorolipids are microbially produced biosurfactants of the glycolipid type that have entered the market in select applications such as detergent or cosmetic formulation ingredients. This study focuses on sophorolipid production by the yeast Starmerella bombicola from stearic acid (C18:0), a low-cost carbon source that is difficult to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 40 publications
(56 reference statements)
1
32
0
6
Order By: Relevance
“…Nevertheless, SL are still a better alternative to Triton X‐100 to be used in this kind of application due to their better environmental profile. The performance of natural SL can be improved by increasing the hydrophobicity of the SL, e.g., using SL mixtures rich in 18:0 molecules (Jiménez‐Peñalver et al, ) or enlarging the fatty acid tail by esterification with alcohols (Koh et al, ). These results confirmed the effectiveness of SL produced from real waste to be used in selected applications.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, SL are still a better alternative to Triton X‐100 to be used in this kind of application due to their better environmental profile. The performance of natural SL can be improved by increasing the hydrophobicity of the SL, e.g., using SL mixtures rich in 18:0 molecules (Jiménez‐Peñalver et al, ) or enlarging the fatty acid tail by esterification with alcohols (Koh et al, ). These results confirmed the effectiveness of SL produced from real waste to be used in selected applications.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reached a sophorolipid yield and productivity of 0.21 g g −1 and 0.58 g L −1 h −1 respectively when using sugar beet molasses and winterization oil cake as carbon sources. With the same experimental set-up, Jiménez-Peñalver et al 33 recently reported that utilization of sorghum bagasse and waste cooking oil as carbon sources could achieve a sophorolipid yield and productivity of 0.56 g g −1 and 0.12 g L −1 h −1 respectively. Although, as compared with submerged fermentation, the results from SSF were not as promising, it is important to note that SSF is a newly developed method.…”
Section: Fermentation Mode Strategy and Specially Designed Bioreactormentioning
confidence: 99%
“…Efforts have been made in mainly three directions: (i) metabolic pathway modification for increasing sophorolipid selectivity; 29,30 (ii) utilization of waste streams as substrates to achieve more sustainable approaches; 28 (iii) fermentation optimization, including selection of fermentation mode, strategy and tailor-made fermentor and/or fermentation unit for improved production titers and productivities. [31][32][33] This review aims to discuss the latest approaches in these aspects which have a critical influence on reduction of the sophorolipid production cost and enhancement Wetting agent 12 Promote leptin synthesis 13,14 Bioremediation (e.g. decontamination of polluted hydrocarbon and heavy metal from soil or mud) [2][3][4]15 Oil recovery in petroleum industry 16,17 Cleansing agent (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Biosurfactants possess similar surface‐active properties as their chemical counterparts, allowing for their use as cleaning, emulsifying, foaming, and dispersing agents. Biosurfactants have several advantages over chemically synthesized surfactants, which are lower toxicity, having specific functional groups with targeted actions, and more effective at extreme temperatures or pH values (Jiménez‐Peñalver et al, ). The commercial potential of biosurfactants is based on these advantages (Mao et al, ; Mondal et al, ; Vijayakumar and Saravanan, ).…”
Section: Introductionmentioning
confidence: 99%